EP1356 Evaluation of doctor-patient communication in a gynaecological oncology outpatient setting. (1st November 2019) - Mulligan, K; Egan, S; Brennan, D; O'Meara, Y; O'Toole, S; ,
Abstract : Introduction/Background: The Irish Society of Gynaecologic Oncology Public and Patient Involvement Group (ISGOPPI) was established 'to achieve a true partnership between public/patients and the society which will promote the quantity and quality of health research and ultimately improve health services and outcomes.' At the groups first workshop, a dominant theme emerged from the patient group centred around doctor-patient communication, in particular the doctor's body language. The aim of this study was to evaluate doctor patient communication within gynaecological oncology services in Ireland. Methodology: An anonymous and confidential 20 question survey was designed by the patient advocacy group ISGOPPI and distributed in three gynaecological oncology outpatient clinics in tertiary referral centres. Results: A total of 84 patients completed the survey. Doctors surveyed ranged from senior house officer to consultant level. Overall women were very satisfied with the communication they had received from their doctor. 85% felt that they the doctor listened to them and took their opinion into account. 84% of patients felt that the doctor's body language was appropriate throughout the consultation. One of the main issues for women surveyed was waiting times. 33% of women waited over an hour to see their doctor and over 30% of women did not receive contact details of the clinical nurse specialist. Conclusion: Overall our study shows that patients in gynae-oncology clinics are satisfied with the communication from their doctors. The main issues for patients were waiting times and contact details for follow up questions. Disclosure: Nothing to disclose.